Stability, sustainability and viability of the Portuguese Football Federation - Silva, Rui (2016)
Purpose: to evaluate and study the viability, stability and the ability of the Portuguese Football Federation (PFF) to generate sustained profits. Methodology: Data were collected based on the Audit Reports of the institution during 2012-2014 and a financial and economic analysis was performed in order to establish some indicators of solvability, profitability and financial balance. Findings: It exists a lack of consistency in managing the profits obtained. We can also suggest that should be given a greater interest to the management of their own intangible assets, as brand management, for example. Practical implications: By making known to leaders and managers of this type of institutions that exists a link between participation in international championships and increase of their profitability may encourage them to better managing these cash inputs in order to decrease the dependence of Governmental financing. We also found that the management of their own intangible assets, as brand management, for example, could probably add more positive financial results.